Research handbook on democracy and development - Crawford, Gordon; Abdulai, Abdul-Gafaru (Edward Elgar Publishing, 2021)
"Exploring and updating the controversial debates about the relationship between democracy and development, this Research Handbook provides clarification on the complex and nuanced interlinkages between political regime type and socio-economic development. Distinguished scholars examine a broad range of issues from multidisciplinary perspectives across Africa, Asia, Europe, Latin America and the Middle East. Analysing the relationship between political regime types, including varieties of democracies and autocracies, and broader development indicators, chapters cover economic growth, poverty and human development, inequality, corruption, conflict, human rights, and environmental sustainability. The Research Handbook examines longstanding and unresolved debates in the field over the past 60 years, as well as investigating contemporary issues of rising global inequalities, the resurgence of authoritarian populism, and the crisis of liberal democracy. Thorough and invigorating, this will be an essential read for social science scholars and students, particularly those studying sociology, politics, economics and global development studies. Policy makers and government officials dealing with foreign affairs and international development will appreciate the detailed case studies the Research Handbook offers."--
Includes bibliographical references and index
Keywords: Erde; Aufsatzsammlung